The State of Art in the Effective Budget Process for Small and Medium-Sized Enterprises - Vuong, Tuan Khanh (International Journal of Economics and Financial Issues, 2023)
The budget process plays a crucial role in the implementation of all the functions within small and medium-sized enterprises (SMEs), such as business, management, operation, manufacturing, etc. The results from this study, identifies that in the budget process the top-down approach of SMEs occupies 33.7%, and the bottom-up approach occupies 26.3%. Meanwhile, SMEs’ method for budget process is the "across approach" (participative), which resulted in 40%, this method is the most popular in comparison with others. Therefore, in the development of the budget process, it is vital to link all the sector functions within the SMEs, as this will facilitate the achievement of the nominated goals and objectives and provide higher-levels of performance. When management and employees work together to develop an effective budget, it improves the key outcomes and overall performance of SMEs. Furthermore, a unified participation approach to budget preparation process development ensures full cooperation and commitment for avoiding asymmetric information and achieving an effective budget process. This study offers academics and practitioners with essential insights for managing company performance, assisting SMEs in evolving as sustainable and competitive players in this new era.